Predictors of Scholastic Achievement of Secondary School Students - Sharma, Princy; Sharma, Darshana (MIER Journal of Educational Studies Trends and Practices, 2021)
The present study aims to find the contribution of self-concept, stress, educational aspirations, parental involvement and guidance needs in predicting the scholastic achievement of secondary school students. The sample for the study comprised 205 students studying in 8th, 9th and 10th classes, selected through random sampling technique. The researchers used Children’s Self Concept Scale (Ahluwalia & Singh, 1986), Student Stress Scale (Akhtar, 2011), Educational Aspiration Test (Khan, 2009), Parental Involvement Scale (Chauhan & Arora, 2009), and a self-constructed Guidance Needs Scale in the study. Findings reveal that self-concept, educational aspirations, and parental involvement have a positive relationship with the scholastic achievement of students and stress and guidance needs have a negative relationship. Multiple linear regression analysis was found significant at 0.01 level of significance. Self-concept, stress, educational aspirations, parental involvement and guidance needs contribute significantly to the variance in the scholastic achievement of the students. Implications of these results for parents, teachers, counsellors and school administrators have been reported in the study.